IMPLEMENTATION OF EARLY CHARACTER EDUCATION IN ELEMENTARY SCHOOL - Melyani Sari Sitepu; Fahrani Aftiansyah (Proceeding International Seminar of Islamic Studies, 2023)
This research is motivated by character education in elementary schools, and the implementation of the application of character education values in learning at SDN 106170 Ajibaho, Patumbak street, Ajibaho Village, Kec. Biru-biru. The purpose of this article is to find out how character education is implemented at SDN 106170 Ajibaho. The method used is a descriptive qualitative research method, so the results are: 1) Character values that are applied and shown are religion, environmental care, responsibility, honesty, and tolerance. 2) The application and concept of character education at SDN 106170 Ajibaho through habituation. The subjects in this research are teachers and students and the object of this research is character education in elementary schools. The implementation of environmental care character education at SDN 106170 Ajibaho can be seen through integration into routine habituation activities carried out at SDN 106170 Ajibaho in the implementation of education.